Estimating Optimum Period of Time Between Maintenances by Using Monte Carlo Simulation Method - Lateef Saleh, Faek (Anbar Journal of Engineering Sciences, 2012)
This work aims to increase the availability of steam generation plant through modifying boiler maintenance plan by determining the optimum period of time between maintenances to achieve maximum availability via simulation approach. Applying simulation approach is an attempt to determine the optimum period of time between schedule maintenances to achieve maximum boiler availability. Therefore, PC program in visual basic language is designed as a tool to the implementation of availability simulation approach. It notes that the boiler availability is increased by (6.9%) in changing the optimum time between scheduled maintenances and inspection to be seven months rather than one year